Stem cells in tissue engineering: Dynamic cultivation requirement - Trišić Dijana; Jokanović Vukoman; Antonijević Đorđe; Marković Dejan (Serbian Medical Society - Dental Section, Belgrade, 2018)
Stem cells have shown great potential for in vitro tissue engineering, regenerative medicine, cell therapy and pharmaceutical applications. All these applications, especially in clinical trials, will require guided production of high-quality cells. Traditional culture techniques and applications have been performed for the majority of primary and established cell lines and standardized for various analyses. Still, these culture conditions are unable to mimic dynamic and specialized three-dimensional microenvironment of the stem cells' niche from in vivo conditions. In an attempt to provide biomimetic microenvironments for stem cells in vitro growth, three-dimensional culture techniques have been developed. In our study advantages of newly developed porous scaffolds as the most promising in vitro imitation of niche that provides physical support, enables cell growth, regeneration and neovascularization, while they are replaced in time with newly created tissue was explained. Furthermore, dynamic cultivation techniques have been described, as new way of cell culturing that will be the main subject of our future research. In that manner, by developing an optimal dynamic culturing method, high-quality new cells and tissues would be possible to obtain, for any future clinical application.